2017
DOI: 10.1038/srep43147
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency torsional Alfvén waves as an energy source for coronal heating

Abstract: The existence of the Sun’s hot atmosphere and the solar wind acceleration continues to be an outstanding problem in solar-astrophysics. Although magnetohydrodynamic (MHD) modes and dissipation of magnetic energy contribute to heating and the mass cycle of the solar atmosphere, yet direct evidence of such processes often generates debate. Ground-based 1-m Swedish Solar Telescope (SST)/CRISP, Hα 6562.8 Å observations reveal, for the first time, the ubiquitous presence of high frequency (~12–42 mHz) torsional mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
118
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(125 citation statements)
references
References 44 publications
(57 reference statements)
7
118
0
Order By: Relevance
“…See also Ofman et al (1995) and Shestov et al (2017) for a similar analysis. However, Alfvén waves are difficult for detection, particularly when high-frequency waves are concerned (Srivastava et al 2017); in an inhomogeneous and structured medium, these waves can experience reflection, mode coupling, phase-mixing and resonant absorption (Ofman et al 1995;Nakariakov et al 1997;Zaqarashvili & Roberts 2006;Goossens et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…See also Ofman et al (1995) and Shestov et al (2017) for a similar analysis. However, Alfvén waves are difficult for detection, particularly when high-frequency waves are concerned (Srivastava et al 2017); in an inhomogeneous and structured medium, these waves can experience reflection, mode coupling, phase-mixing and resonant absorption (Ofman et al 1995;Nakariakov et al 1997;Zaqarashvili & Roberts 2006;Goossens et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Currently there are mainly two competing proposals: heating through small‐scale reconnection (Parker, 1988) and dissipation of waves. The ubiquitous presence of low‐frequency coronal waves has been recently revealed through advanced ground‐based and space observations (e.g., Tomczyk et al, 2007; McIntosh et al, 2011; Tian H et al, 2012; Hahn et al, 2012; Morton et al, 2015; Jiao FR et al, 2015; Srivastava et al, 2017). While high‐frequency waves with a period shorter than a few seconds are rarely reported in the quiet corona, due obviously to the fact that most coronal observations use a cadence lower than 10 seconds.…”
mentioning
confidence: 99%
“…In solar physics, Alfvén waves are mainly considered to be candidates for coronal heating due to their ability to freely propagate from lower layers of the solar atmosphere to the corona (e.g., Ruderman 1999;Srivastava et al 2017). For example, Copil et al (2008) suggested that propagating Alfvén waves could locally heat coronal plasma threads.…”
Section: Introductionmentioning
confidence: 99%